Formação docente e saberes (re)construídos no atendimento educacional especializado em Delmiro Gouveia - Alagoas - Nascimento, Patrícia do (2020)
This dissertation, aimed to understand the (re) constructed knowledge of the teachers of Specialized Educational Service (SES), with a view to the identification of their conceptions about the continued formation offered by the Municipal Education Secretariat of Delmiro Gouveia (MESDG). As for the specific objectives, we list: map the profile of teachers working in the SES, in the Multifunctional Resource Rooms (MRR), of the municipal schools of Delmiro Gouveia; to identify the theoretical-conceptual field of training and the teaching knowledge necessary for the SES and to analyze the continuing training offered by MESDG to the teachers of the SES. The theoretical framework is based on authors from the area of special education in an inclusive perspective, among which are Mantoan (2015); Bianchetti (2012) and Bueno (2011) and in scholars who discuss teacher training and knowledge, highlighting Tardif (2014); Imbernón (2016) and Nóvoa (2019). The methodology adopted was the bibliographic study, with a qualitative approach, whose investigative instruments consisted of the realization of semi-structured interviews with the two coordinators, five teachers and one teacher from the SES. For the data's interpretation was based on Bardin's content analysis. The interpretation of the data was based on the content analysis of Bardin (2016), based on the epistemology of professional practice advocated by Tardif (2014). The results of the research allowed us to trace the profile of the participants, revealing that both the coordinators and the teachers have appropriate training to work in the ESA, meeting the proposed legislation. It also made it possible to understand, from their perspective, how continued training is offered, planned and developed, evidencing the teaching knowledge mobilized and (re)constructed in the pedagogical practice developed in the RMS. It was found that these teachers use more of experiential knowledge and (re) build from the studies and experiences experienced in continuing education.